Legal regulation of the budget process under the conditions of marital state (Law and Safety, 2022)
The presented publication analyzes the budget process under the conditions of martial law in Ukraine and its legal support. It is argued that the budget process in modern conditions is characterized by such features as: systematicity, cyclicality, legal character, stagedness. Budget process as a set of systematic, consistent and interdependent actions is implemented by relevant entities. In particular, we are talking about the participants in the budget process, the list of which is fixed in the prescriptions of the budget legislation (part 3 of article 19 of the BC of Ukraine). It is noted that such a list is not complete and does not take into account all participants in the budget process, especially those whose activities are related to the limited management of budget funds.It is emphasized that since the beginning of the armed aggression of the Russian Federation against Ukraine, the budget legislation has undergone significant changes. This characteristic of the budget process can be clearly demonstrated on specific examples. The signs of the budget process are determined. It has been established that the budget process and the legislative process are not identical. The features of the functioning of the reserve fund of the state budget in modern conditions are considered. It is argued that in order to ensure the effective functioning of the fund of inland waterways, formed as part of the special fund of the state budget, proper legal regulation is necessary. In particular, it refers to the adoption of the Resolution of the Cabinet of Ministers of Ukraine “On approval of the Procedure for the allocation of funds of the state fund of inland waterways” as an important prerequisite for the functioning of the specified fund.
Keywords: budget process; martial law; features of the budget process; participants of the budget process; stages; budget reserve fund; special budget fund.